Prevention and management of anthracycline induced cardiotoxicity: A review - Ian Osoro; Amit Sharma; Mohammad Amir; Manisha Vohra; Ranjeet Kumar; Hardik Kumar; Abrar Zargar; Hemraj Bangar (Health Sciences Review, 2022)
Anthracycline drugs such as doxorubicin, epirubicin, idarubicin play a highly significant role in chemotherapy. These agents have been in use for about six decades now and have proven to be greatly effective. However, progressive cardiotoxicity has been outlined to be the greatest concern of these drugs during the treatment, especially with first time users. Although it is usually noticed in recent users, research has shown that it can occur after a longer duration due to the cumulation of the dose which is less studied as compared to the early onset studies. Despite the vast effort in terms of research that has been conducted to ensure safety, a specific treatment regimen is yet to be drafted due to divergent ideologies within the field.The development of cardio-oncology, a branch of cardiology that specializes in the prevention or treatment of cardiac issues due to cancer treatment, has brought more understanding about molecular mechanisms behind anthracycline-induced cardiotoxicity (AIC). There have been divergent proposed mechanisms such as generation of ROS, calcium homeostasis dysregulation, autophagy and mitochondrial dynamism impairment. Interestingly, all these mechanisms converge on deregulation of mitochondrial function which needs wider research for verification that is yet to be conducted. Clinical symptoms evaluation, acquisition scans, systolic function detection by echocardiography and magnetic resonance imaging are the main ways of evaluating AIC.Our methodology involved a preliminary search on the PubMed, OVID Medline, Embase, ScienceDirect, Web of Science, and Google Scholar databases where keywords such as “DOX induced cardiotoxicity, anthracycline induced cardiotoxicity and cardiotoxicity prevention and management” were used.This review outlines the recent steps in the prevention and management of anthracycline cardiotoxicity and identifies research gaps that necessitate the need for further research. Our results suggest that great advancement has been achieved over the years but still there is need for more prospective researches that have involve more patients for consensus to be achieved. Also, there is need for translation of the knowledge into practice which is yet to be duly fulfilled.